2018
DOI: 10.1002/2211-5463.12540
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of BMP‐1/tolloid‐like proteinases: efficacy, selectivity and cellular toxicity

Abstract: BMP ‐1/tolloid‐like proteinases belong to the astacin family of human metalloproteinases, together with meprins and ovastacin. They represent promising targets to treat or prevent a wide range of diseases such as fibrotic disorders or cancer. However, the study of their pathophysiological roles is still impaired by the lack of well‐characterized inhibitors and the questions that remain regarding their selectivity and in vivo efficiency. As a first step towards the identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
(79 reference statements)
0
17
0
Order By: Relevance
“…This can be avoided by using plates coated with poly-d-lysine (37), but the mechanism underlying this observation has remained unclear. As a first step to elucidate the BMP-1-induced loss of adhesion, we added the synthetic BMP-1 inhibitor S33A [a hydroxamate inhibitor referred to as hxt in this study (31,39)] to the culture medium and observed that the BMP-1-producing cells could be efficiently maintained in the adherent state in the presence of the inhibitor (Fig. 1A).…”
Section: Bmp-1 Disrupts Cell Adhesion In 293-ebna and Ht1080 Cellsmentioning
confidence: 99%
“…This can be avoided by using plates coated with poly-d-lysine (37), but the mechanism underlying this observation has remained unclear. As a first step to elucidate the BMP-1-induced loss of adhesion, we added the synthetic BMP-1 inhibitor S33A [a hydroxamate inhibitor referred to as hxt in this study (31,39)] to the culture medium and observed that the BMP-1-producing cells could be efficiently maintained in the adherent state in the presence of the inhibitor (Fig. 1A).…”
Section: Bmp-1 Disrupts Cell Adhesion In 293-ebna and Ht1080 Cellsmentioning
confidence: 99%
“…To clarify the functions of BTPs in hepatic differentiation in the future, it may be helpful to create a TLL1 and BMP1 double‐knockout human iPS cell line. Methods for using BTP‐specific inhibitors may also be effective.…”
Section: Discussionmentioning
confidence: 99%
“…There has been little research thus far examining the use of BMP1 inhibitors in combination with chemotherapeutics to specifically treat LOX/LOXL1 overexpressing cancers. This may be due, at least in part, to the difficulty in finding inhibitors of BMP1 that are selective, potent and cost effective [ 164 ], and the role that BMP1 plays in a range of other vital cellular processes including bone and cartilage development and repair [ 165 ]. Alternatively, increases in BMP1 may have tumour suppressive effects in Ras transformed cancers, where post-translational processing in cells highly expressing LOX and LOXL1 would increase levels of the tumour suppressive LOX pro-peptide.…”
Section: Approaches To Target the Lysyl Oxidases Directly And Indimentioning
confidence: 99%